2024
DOI: 10.1007/s40477-023-00852-x
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative characteristics of CEUS for renal cell carcinoma and angiomyolipoma: a narrative review

Piervito Dipinto,
Vittorio Canale,
Rocco Minelli
et al.

Abstract: Incidental findings of renal masses are increasing. However, a substantial portion of surgically treated renal masses turn out to be benign on histopathological examination. Thus, there is a clear need for improved pre-surgical assessment to minimize unnecessary invasive procedures. The challenge intensifies when distinguishing between renal cell carcinoma (RCC) and angiomyolipoma (AML) in renal lesions smaller than 4 cm with minimal adipose tissue. In such cases, contrast-enhanced ultrasound (CEUS) has emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The results of studies conducted in the recent past have confirmed that the presence of a pseudo-capsule, rapid wash-out, and high and heterogeneous enhancement on CEUS examination indicate the malignant nature of the lesion and most often indicate a diagnosis of renal cell carcinoma [19,22,24]. In contrast, benign lesions usually show slow centripetal enhancement, homogeneous peak enhancement, and gradual wash-out [19,24].…”
Section: Solid Renal Lesions In Ceusmentioning
confidence: 74%
See 2 more Smart Citations
“…The results of studies conducted in the recent past have confirmed that the presence of a pseudo-capsule, rapid wash-out, and high and heterogeneous enhancement on CEUS examination indicate the malignant nature of the lesion and most often indicate a diagnosis of renal cell carcinoma [19,22,24]. In contrast, benign lesions usually show slow centripetal enhancement, homogeneous peak enhancement, and gradual wash-out [19,24].…”
Section: Solid Renal Lesions In Ceusmentioning
confidence: 74%
“…The most common benign solid tumors of the kidney are AML and renal oncocytoma [18]. AMLs are hamartomatous benign tumors composed of newly formed vessels, smooth muscle cells, and well-differentiated adipose tissue [19]. About 80% of AMLs occur as isolated entities, but they can also be associated with the tuberous sclerosis complex [20].…”
Section: Solid Renal Lesions In Ceusmentioning
confidence: 99%
See 1 more Smart Citation
“…CEUS is a useful method to visualize the contrast enhancement features of RCC subtypes in adults 23 , 24 . Clear cell RCCs show typical hyperenhancement with wash-out, while papillary RCCs and chromophobic RCCs show hypoenhancement throughout the enhancement phases 10 , 25 .…”
Section: Discussionmentioning
confidence: 99%